(untitled) (Journal of the College of Basic Education, 2026)
The current research aims to identify: 1- Ethical violation among Al-Mustansiriyah University students. 2- The significance of the differences in ethical violation among university students at the significance level (0.05) according to the gender variable (male and female students). 3- Sarcastic humor among the students of Al-Mustansiriyah University. 4- Significance of differences in sarcastic humor among university students at the level of significance (0.05) according to the gender variable (male and female students). 5- The nature of the relationship between ethical violation and sarcastic humor among university students. The current research is limited to male and female students of Al-Mustansiriyah University for the academic year 2023-2024, and to achieve this, the descriptive method based on analysis and interpretation was used, and the current research community includes students of the morning preliminary studies at Al-Mustansiriyah University, and the original community consisted of (34583) male and female students distributed According to the faculties of the university, a sample representing the research community of (400) male and female students were selected in a random and stratified manner, the ethical violation scale prepared by Al-Zughaibi (2013) was adopted, and the scale in its final form consisted of (28) paragraphs , The researcher also adopted the sarcastic humor scale prepared by Saleh (2016), the scale in its final form consisted of (34) paragraphs, the results found that the research sample of students of the Egyptian University have a low level of ethical violation among university students, and there are differences in ethical violation according to the variable of gender, and in favor of male students and in favor of males, and that the current research sample of university students have the trait of sarcastic fun, and there are statistically significant differences in sarcastic fun according to the gender variable (male and female students), and in favor of male students, and that the correlation coefficient between ethical violation and sarcastic fun is a positive and statistically significant correlation coefficient. According to the results, the researcher came up with a set of recommendations and suggestions.